The Oxford handbook of language attrition - Köpke, Barbara; Schmid, Monika S.; Cherciov, Mirela 1978-; Karayayla, Tugba; Keijzer, Merel; De Leeuw, Esther; Mehotcheva, Teodora H.; Montrul, Silvina; Polinsky, Maria (Oxford handbooks in linguistics., 2022)
This volume is the first handbook dedicated to language attrition, the study of how a speaker's language may be affected by crosslinguistic interference and non-use. Topics covered include theoretical implications, psycho- and neurolinguistic approaches, linguistic and extralinguistic factors, L2 attrition, and heritage languages.